Effect of CArbocisteine in Prevention of exaceRbation of chronic obstructive pulmonary disease (CAPRI study): An observational study. (April 2016) - Esposito, Antonietta; Valentino, Maria Rosaria; Bruzzese, Dario; Bocchino, Marialuisa; Ponticiello, Antonio; Stanziola, Anna; Sanduzzi, Alessandro
Abstract: Background: Chronic Obstructive Pulmonary Disease (COPD) is a chronic and progressive lung disease characterized by irreversible airflow obstruction, airway inflammation, oxidative stress and, often, mucus hypersecretion. The aim of this study is to determine if carbocisteine, a mucolytic and antioxidant agent, administered daily for 12 months, can reduce exacerbation frequency in COPD patients. Methods: This observational study was conducted in Naples (population approximately 1000, 000), Italy. It included 85 out-patients (mean age of 67.8 ± 8.6 years) followed by Clinic of Respiratory Diseases of the University Federico II. Every patient underwent spirometry demonstrating airflow obstruction not fully reversible according to ERS/ATS criteria for COPD diagnosis (Tiffenau index less than 70% after administration of salbutamol, a beta2 agonist drug). Patients enrolled had diagnosed COPD since 2 years and suffered at least one exacerbation in the previous year. None of the patients had been treated with carbocisteine or other mucolytic agent for a longer period of time than 7 days and no more than 4 times in the previous year to the enrollment. All of them assumed daily 2.7 g of carbocisteine lysine salt for a year in addition to their basic therapy. Results: The comparison of exacerbation frequency between the previous year (T0) and the end of study treatment (T12), documents a statistically significant reduction of exacerbations(number of exacerbations at T0: 2 [1, 3] vs number of exacerbations at T12: 1 [1, 2]; p < 0.001).Quality of life was also reported and showed a statistically significant improvement at the end of the study (p < 0.001).We did not find correlation between reducing exacerbation frequency and exposure to cigarette smoking, passive smoking exposure in childhood, the use of inhaled steroids, the level of education of our patients and the GOLD stadium. Interpretation: Daily administration of a mucolytic drug such as carbocisteine for prolonged periods in addition to the bronchodilator therapy can be considered a good strategy for reducing exacerbation frequency in COPD.